Implementation process and lessons learned in the determination of educational cost using modified activity-based costing (ABC) / Ruhanita Maelah ...[et al.] - Maelah, Ruhanita; Md Auzair, Sofiah Sofiah; Mohd Amir, Amizawati; Ahmad, Azlina Azlina (UiTM Press, 2017)
Putting in place accurate cost information for the outputs of universities is no longer a choice but a necessity if a university is to have a worldclass management system. Nevertheless, the current costing systems are not designed to support management-related information with fund accounting and budgetary control systems dominating the mind-sets of the administrators of universities. In support of an autonomous pathway for public universities in Malaysia, Universiti Kebangsaan Malaysia has piloted an educational cost determination exercise using the activity based costing (ABC) system. Instead of proposing a major overhaul to the system, an ABC model that takes into consideration existing limitations was developed. While far from being perfect, the model is workable within certain limitations. This study examines the process involved in the exercise of determining educational cost based on the modified ABC approach. Nine critical steps are explained and the lessons learned from the exercise are highlighted. This study contributes to the theoretical knowledge by providing empirical evidence of the application of ABC in a service setting, or, more specifically, in a university. In terms of practice, this study provides guidelines concerning the determination of educational cost to interested parties including the university’s management, Ministry of Education and other universities.